Near-Infrared-Emissive AIE Bioconjugates: Recent Advances and Perspectives - Wenshuai Luo; Yonghong Tan; Yixiong Gui; Dingyuan Yan; Dong Wang; Ben Zhong Tang (Molecules, 2022)
Near-infrared (NIR) fluorescence materials have exhibited formidable power in the field of biomedicine, benefiting from their merits of low autofluorescence background, reduced photon scattering, and deeper penetration depth. Fluorophores possessing planar conformation may confront the shortcomings of aggregation-caused quenching effects at the aggregate level. Fortunately, the concept of aggregation-induced emission (AIE) thoroughly reverses this dilemma. AIE bioconjugates referring to the combination of luminogens showing an AIE nature with biomolecules possessing specific functionalities are generated via the covalent conjugation between AIEgens and functional biological species, covering carbohydrates, peptides, proteins, DNA, and so on. This perfect integration breeds unique superiorities containing high brightness, good water solubility, versatile functionalities, and prominent biosafety. In this review, we summarize the recent progresses of NIR-emissive AIE bioconjugates focusing on their design principles and biomedical applications. Furthermore, a brief prospect of the challenges and opportunities of AIE bioconjugates for a wide range of biomedical applications is presented.